Do Chinese employers avoid hiring overqualified workers? Evidence from an internet job board - Kailing Shen; Peter Joseph Kuhn (Institute for the Study of Labor (IZA), 2012)
Can having more education than a job requires reduce one's chances of being offered the job? We study this question in a sample of applications to jobs that are posted on an urban Chinese website. We find that being overqualified in this way does not reduce the success rates of university-educated jobseekers applying to college-level jobs, but that it does hurt college-educated workers' chances when applying to jobs requiring technical school, which involves three fewer years of education than college. Our results highlight a difficult situation faced by the recent large cohort of college-educated Chinese workers: They seem to fare poorly in the competition for jobs, both when pitted against more-educated university graduates, and when pitted against less-educated technical school graduates.
Keywords: J64; J24; 330; overqualification; job search; internet; China; Unterbeschäftigung; Akademiker; Arbeitsnachfrage; Internet; Arbeitsuche; China